Effect of silica (SiO2) filler on thermal stability of polysiloxane composites - Azmi, Mohd Azham; Yahya, S.M.; Ahmad, Sufizar; Mahzan, Shahruddin; Taib, M.; Abd.Rahman, Hamimah; Taib, Hariati (Akademia Baru, 2018)
Thermal stability of composites are influenced by the types and properties of filler used. In this study Silica (SiO2) namely CS was used to improve the thermal stability of Polysiloxane (PoS) panel. The PoS/CS composites were fabricated by mixing PoS and CS with filler loading of 2wt% to 12 wt%. PoS/CS composites are then cast using close mold technique and cured at room temperature (RT), 65˚C and 100˚C. The CS were characterized for X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), and Fourier Transform Infrared (FTIR) technique. The thermal stability of PoS/CS composites were identified via Thermal Gravimetric Analysis (TGA). It was found that, CS improved the thermal stability of PoS by increased decomposition temperature and decreased relative mass loss percentage. CS as a filler, replaced and reduced the hydroxyl group in the composites panel to significantly improved the thermal stability. Hence, the good thermal stability of CS also helps to improve PoS composites thermal properties. The interference of hydroxyl crosslink during curing was also found to affect the thermal stability. Thus, the high temperature curing (65˚C and 100˚C) were indeed unstable due to disruption of cross link process and thus affect the filler dispersion and cause aggregations. PoS/CS/RT composites were found to show the stable and linear profile of thermal stability compare to PoS/CS/65˚C and PoS/CS/100 ˚C. Thus the thermal stability of polysiloxane had improved by using CS as a filler and cured at RT.